Non-thermal fluctuations in plasma density near the temperature minimum of the solar atmosphere - Kyzyurov, Yu.V. (Кинематика и физика небесных тел, 2005)
We consider the formation of plasma-density fluctuations by non-thermal motions of gas near the temperature minimum of the solar atmosphere. For the inertial wavenumber range of turbulent velocity field of gas, an analytic expression for the one-dimensional (1D) spectrum of the fluctuations is obtained. This expression is used to predict the shape of the 1D horizontal spectrum of the fluctuations under three values of magnetic field strength: 5, 50, and 250 G. Also, estimates of the rms level of the fluctuations are made. It is shown that the increase in magnetic field has to alter the shape of the horizontal spectrum and to increase the level of the plasma-density fluctuations.